Hadith #433 - Sahih Muslim - al-Husain bin 'Abdullah bin 'Ubaidullah الحسين بن عبد الله بن عبيد الله بن عباس (Sahih Muslim)
I was with Sa’id b. Jubair when he said: Who amongst you saw a star shooting last night? I said: It was I; then I said: I was in fact not (busy) in prayer, but was stung by a scorpion (and that is the reason why I was awake and had a glimpse of the shooting star). He said: Then what did you do? I said: I practised charm. He said: What urged you to do this? I said: (I did this according to the implied suggestion) of the hadith which al-Shu’ba narrated. He said: What did al-Shu’ba narrate to
Grade: Sahih